IMPROVING MEDICAL ASSISTANCE EFFICIENCY THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN EMERGENCY SITUATIONS (International journal of artificial intelligence, 2026)
This article examines the significance and potential of using artificial intelligence (AI) technologies in providing medical assistance during emergency situations. It presents information on AI and its capabilities. The development of modern information technologies creates new opportunities in healthcare. Specifically, AI can be used to rapidly assess patients’ conditions, detect diseases, perform accurate diagnoses, and efficiently organize medical services. The article highlights the role of AI systems in making timely decisions during emergencies, optimally allocating medical resources, and saving human lives. Additionally, the advantages, practical applications, and future development prospects of these technologies are discussed.